Rapid assessment of insect pollination services to inform decision‐making. Issue 4 (8th March 2022) - Ratto, Fabrizia; Breeze, Tom D.; Cole, Lorna J.; Garratt, Michael P. D.; Kleijn, David; Kunin, Bill; Michez, Denis; O'Connor, Rory; Ollerton, Jeff; Paxton, Robert J.; Poppy, Guy M.; Potts, Simon G.; et al.
Abstract: Pollinator declines have prompted efforts to assess how land‐use change affects insect pollinators and pollination services in agricultural landscapes. Yet many tools to measure insect pollination services require substantial landscape‐scale data and technical expertise. In expert workshops, 3 straightforward methods (desk‐based method, field survey, and empirical manipulation with exclusion experiments) for rapid insect pollination assessment at site scale were developed to provide an adaptable framework that is accessible to nonspecialist with limited resources. These methods were designed for TESSA (Toolkit for Ecosystem Service Site‐Based Assessment) and allow comparative assessment of pollination services at a site of conservation interest and in its most plausible alternative state (e.g., converted to agricultural land). We applied the methods at a nature reserve in the United Kingdom to estimate the value of insect pollination services provided by the reserve. The economic value of pollination services provided by the reserve ranged from US$6163 to US$11, 546/year. The conversion of the reserve to arable land would provide no insect pollination services and a net annual benefit from insect‐pollinated crop production of approximately $1542/year (US$24∙ha –1 ∙year –1 ). The methods had wide applicability and were readily adapted to different insect‐pollinated crops: rape ( Brassica napus ) and beans ( Vicia faba ) crops. All methods were rapidly employed under a low budget. The relatively less robust methods that required fewer resources yielded higher estimates of annual insect pollination benefit. Abstract : Article impact statement : Insect pollination services can be assessed rapidly under varying budgets with desk‐based methods, field surveys, and exclusion experiments. Abstract : Diversidad y Conservación de Gasterópodos Subterráneos de Agua Dulce en los Estados Unidos y en México Resumen: Las declinaciones de los polinizadores han impulsado los esfuerzos por evaluar cómo el cambio del uso de suelo afecta a los insectos polinizadores y los servicios de polinización en los paisajes agrícolas. Aun así, muchas de las herramientas para medir los servicios de los insectos polinizadores requieren datos sustanciales a escala de paisaje y el conocimiento de expertos. Desarrollamos tres métodos sencillos (método de gabinete, censo de campo y manipulación empírica con experimentos de exclusión) durante algunos talleres de expertos para la evaluación rápida de la polinización por insectos a escala de sitio con el objetivo de proporcionar un marco de trabajo adaptable y accesible para quienes no son especialistas y cuentan con recursos limitados. Estos métodos fueron diseñados para TESSA (Toolkit for Ecosystem Service Site‐Based Assessment, en inglés) y permiten la evaluación comparativa de los servicios de polinización en los sitios de interés para la conservación y su estado alternativo más plausible (p. ej.: convertido a suelo agrícola). Aplicamos los métodos en una reserva natural del Reino Unido para estimar el valor de los servicios de polinización por insectos que proporciona la reserva. El valor económico de los servicios de polinización que proporciona la reserva varió desde US$6, 163 a US$11, 546 al año ‐1 . La conversión de la reserva a suelo arable no proporcionaría servicios de polinización por insectos, pero sí un beneficio anual neto a partir de la producción de cultivos polinizados por insectos de aproximadamente $1, 542 al año ‐1 (US$24 ha ‐1 año ‐1 ). Los métodos tuvieron una aplicabilidad generalizada y estaban ya adaptados a los diferentes cultivos polinizados por insectos: cultivos de colza ( Brassica napus ) y habas ( Vicia faba ). Todos los métodos pudieron usarse con bajo presupuesto. Los métodos relativamente menos robustos que requirieron menos recursos produjeron estimados más elevados del beneficio anual de la polinización por insectos. 【摘要】: 昆虫授粉服务的快速评估为决策提供依据 授粉者数量下降推动了评估土地利用变化如何影响农业景观中昆虫授粉者和授粉服务的研究工作。然而, 许多评估昆虫授粉服务的工具都需要大量景观尺度的数据和专业技术。我们通过专家研讨会开发了3种简单的方法(案头研究方法、野外调查和利用排除性实验的经验操作), 可用于快速评估研究站点的昆虫授粉情况, 为资源有限的非专业人员提供了一个适应性框架。我们的方法是为生态系统服务站点评估工具包(TESSA)设计的, 可以在具有保护意义的站点和其最合理的替代状态下(如转换为农业用地)对授粉服务进行比较评估。我们在英国一个自然保护区应用这些方法估计了该保护区提供的昆虫授粉服务的价值。结果显示, 保护区提供的授粉服务的经济价值从6, 163美元/年到11, 546美元/年不等。保护区如果转换为耕地, 则不能提供昆虫授粉服务, 而昆虫授粉作物的生产则可以提供的约1, 542美元/年(24美元/公顷/年)的年净收益。我们的方法具有广泛的适用性, 可用于不同的昆虫授粉作物, 如油菜( Brassica napus )和蚕豆( Vicia faba )。以上方法都可以在低预算的情况下快速使用。需要资源较少但相对较不稳健的方法会得到更高的昆虫授粉年效益估计值。【翻译:胡怡思;审校:聂永刚】